Plights of Marginalised Limbu Community in Subba’s “Laato Pahaada” [Dumb Hill] - Rai, Jiwan Kumar (JODEM: Journal of Language and Literature, 2020)
The title story “Laato Pahaada” [“Dumb Hill”] selected from Upendra Subba’s anthology of stories Laato Pahaada [Dumb Hill] represents plights – pains, sufferings, tortures and difficulties – of ethnic Limbu community at the margin under the dominance of mainstream culture and various forms of repressive and ideological state apparatuses. So, this study aims to find out the responsible factors that compel the ethnic Limbu community to remain illiterate and go through numerous pains, sufferings, tortures and humiliation. Similarly, it aims to analyse how the illiterate and poor Limbu people suffer and get tortured by the cultural practices and apparatuses of the state power. In order to achieve the designed objectives and reach to a conclusion, Cultural Studies has been used as an overall theoretical approach. Particularly, Althusser’s concepts of ideology – repressive and ideological state apparatuses, and Michel Foucault’s idea of discourse and power have been used as theoretical tools for the analysis of the text. This study provides a new insight to see and understand the plights of the people at the margin from a new perspective; and to realize about the importance of marginalized cultures. Innocent Limbu people go through sufferings of illiteracy, poverty and difficulties due to the mono-cultural values and mono-lingual education system of state power which are effectively practiced by the means of both repressive and ideological apparatuses.